A TECHNOLOGICAL UNDULATIVE INDUCTION ACCELERATOR FOR COMMERCIAL APPLICATIONS - Kulish, V.V.; Chemerys, V.T.; Gubanov, I.V.; Kryzhanovsky, V.M. (Proceedings of National Aviation University (archive), 2005)
The results of analysis of the electron undulative induction accelerator are presented in the paper. It is shown, in particular, that a wide spectrum of technological systems (destined for natural and wastewater purification, medicine equipment and preparations, etc.) can be constructed on the basis of undulative induction accelerator. Characteristic features of these systems are commercial attractiveness, high level of efficiency and relative compactness. One variant of design of the undulative induction accelerator is described and discussed.